Fracture mechanics analysis of defence hole system for a uniaxially loaded plate using boundary element method - Low, Joseph Jian Liang (Nanyang Technological University, 2020)
Fatigue failure in engineering components usually arises at the root of a geometrical discontinuity.It is therefore essential that designers are able to predict and reduce these stress concentration in order to enhance the working life of these components. Stress concentrations factors will be determined for a range of auxiliary defence hole systems. Cracks will be modelled in these highly stressed region and the fracture characterizing parameter will be determined using linear elastic frature mechanics theory and the boundary element methods.